BlsA Is a Low to Moderate Temperature Blue Light Photoreceptor in the Human Pathogen Acinetobacter baumannii - Golic, Adrián E.; Valle, Lorena; Jaime, Paula C.; Álvarez, Clarisa E.; Parodi, Clarisa; Borsarelli, Claudio D.; Abatedaga, Inés; Mussi, María Alejandra (Frontiers in Microbiology, 2019)
Light is an environmental signal that produces extensive effects on the physiology of the human pathogen Acinetobacter baumannii. Many of the bacterial responses to light depend on BlsA, a blue-light- using FAD (BLUF)-type photoreceptor, which also integrates temperature signals. In this work, we disclose novel mechanistic aspects of the function of BlsA. First, we show that light modulation of motility occurs only at temperatures lower than 24ºC, a phenotype depending on BlsA. Second, blsA transcript levels were significantly reduced at temperatures higher than 25ºC, in agreement with BlsA protein levels in the cell, which were undetectable at 26ºC and higher temperatures. Also, quantum yield of photo‐activation of BlsA (lBlsA) between 14ºC and 37ºC, showed that BlsA photoactivity is greatly compromised at 25ºC and absent above 28ºC. Fluorescence emission and anisotropy of the cofactor together with the intrinsic protein fluorescence studies suggest that the FAD binding site is more susceptible to structural changes caused by increments in temperature than other parts of the protein. Moreover, BlsA itself gains structural instability and aggregates aggressively at temperatures above 30ºC. Overall, BlsA is a low to moderate temperature photoreceptor, whose functioning is highly regulated in the cell, with control points at expression of the cognate gene as well as photoactivity.